Islamic capitalism: an approaching truth or an expectant panorama for Islamic finance – a case of Pakistan and Malaysia - Muhammad, Awais; Yaqub, Asad; Iftikhar, Umer; Khalid Bhatti, Omar; Mohd Thas Thaker, Mohamed Asmy (CADDO GAP Press USA, 2022)
The investigation of future capitalism in the wake of Islam is rather complicated. The difference of interests and difference of opinions between secular scholars and fiqh scholars can stymie the progress of innovation. Nevertheless, a harmony between their intellectual views can prove to be a boon for encouraging Islamic financial elements. This paper scrutinizes an alternative capitalist structure as one of the basic and fundamental key elements for Islamic finance. In this study, interview-based multi case-study method is used, which is based on qualitative approach. This study concludes that Islam promotes the concept of risk sharing in trading and other financial activities, which may lead to lessen the burden on an individual. However, external factors are playing major roles in both of the countries as conventional system is very strong around the globe.